RNA-containing extracellular vesicles in infection - Kayo Schemiko Almeida; Suélen Andreia Rossi; Lysangela Ronalte Alves (RNA Biology)
Extracellular vesicles (EVs) are membrane-bound particles released by cells that play vital roles in intercellular communication by transporting diverse biologically active molecules, including RNA molecules, including mRNA, miRNA, lncRNA, and other regulatory RNAs. These RNA types are protected within the lipid bilayer of EVs, ensuring their stability and enabling long-distance cellular interactions. Notably, EVs play roles in infection, where pathogens and host cells use EV-mediated RNA transfer to influence immune responses and disease outcomes. For example, bacterial EVs play a crucial role in infection by modulating host immune responses and facilitating pathogen invasion. This review explores the complex interactions between EV-associated RNA and host-pathogen dynamics in bacteria, parasites, and fungi, aiming to uncover molecular mechanisms in infectious diseases and potential therapeutic targets.